Pathological mechanisms of left main stent failure. (15th July 2018) - Mori, Hiroyoshi; Torii, Sho; Harari, Emanuel; Jinnouchi, Hiroyuki; Brauman, Ryan; Smith, Samantha; Kutys, Robert; Fowler, David; Romero, Maria; Virmani, Renu; Finn, Aloke V.
Abstract: Background: Despite the increasing use of left main (LM) percutaneous coronary intervention (LM-PCI), there have been no pathological studies devoted to understanding the causes of LM stent failure. We aimed to systematically determine the pathological mechanisms of LM stent failure. Methods and results: From the CVPath Stent registry, a total of 46 lesions were identified to have LM-PCI. Pathologic stent failure (PSF) was defined as stent thrombosis, restenosis and in-stent chronic total occlusion (CTO). Failed and patent LM stented lesions were pathologically assessed to determine predictors of PSF. Malapposition and uncovered struts were numerically greater in the LM ostium, body, and bifurcation while neointimal thickness was relatively greater in bifurcation and proximal circumflex. In this study cohort, half of the lesions ( n  = 23) showed PSF. Stent thrombosis (ST, n  = 18) was the major mode of PSF followed by in-stent CTO ( n  = 4) and restenosis (n = 1). Failed lesions showed significantly greater prevalence of malapposition >20% of struts/section (65% vs. 13%, P  < 0.01), stent struts crossing an ostial side branch >30% of the circumference (48% vs. 13%, P < 0.01) and uncovered struts >30% (57% vs. 18%, P  = 0.03). In multivariate analysis, the prevalence of malapposition >20% was the strongest risk factor for PSF (Odds ratio 8.0, 95% confidence interval 1.8–45.4, P  < 0.01) followed by struts crossing an ostial side branch >30% (Odds ratio 4.2, 95% confidence interval 0.8–24.7, P  = 0.09). Conclusion: Our data demonstrate the main pathological predictors for LM stent failure are malapposition and struts crossing an ostial side branch and suggest that imaging-guided PCI may be important. Highlights: There have been no pathological studies focusing onthe causes of stent failure in left main coronary artery disease. Failed and patent stented lesions were pathologically assessed from CVPathstent registry (n = 46). In multivariate analysis, malapposition >20%struts/section was the strongest predictor of stent failure (OR 8.0, P  < 0.01).